Isolasi dan Identifikasi Senyawa dari Ekstrak Etanol Daun Mareme (Glochidion arborescens Blume.) - Haryoto, H; Ambarsari, Niati (Prosiding University Research Colloquium, 2022)
Mareme (Glochidion arborescens Blume.) is one of wild plants growing in yard. The leaves are able to be used as traditional medicine since it is considered containing secondary metabolites, such as flavonoids, phenols, alkaloids, saponins, tannins, steroids, triterpenoids, as well quinones. FT-IR (Fourier Transform Infrared Spectroscopy) is used to identify the functional groups in a sample and secondary metabolites of medicinal plants. The objective of study was to identify Mareme leaves (Glochidion arborescens Blume.) isolate seen from functional group. Mareme (Glochidion arborescens Blume.) leaves powder was extracted using maceration method, and then thick extract was fractionated using Vacuum Liquid Chromatography (VLC) and isolated using a chromatotron. FT-IR was used to identify Mareme leaves isolate. Mareme leaves (Glochidion arborescens Blume.) thick extract obtained was 95,52 grams, non-polar fraction was 3,75 grams, semi-polar fraction was 3,90 grams, polar fraction was 3,25 grams, as well isolate was 850 mg. The analysis results by using FT-IR indicate that -OH, -CH aliphatic, -C=O ester and -C-O, active isolates of Mareme leaves (Glochidion arborescens Blume.) are suspected of containing flavonoid compound of flavone group.